The Students’Perception of Using E-book to Improve Students’ ReadingSkill ( A Descriptive Study at the 2nd And 4th of English Study Program of Prof.Dr. Hazairin, SH University Bengkulu ) - Utami, Elva; Marita, Yosi; kencana, Nila; Syukur, Yuneva; Fadriando, Fadhil (Edu-Ling: Journal of English Education and Linguistics, 2023)
The purpose of this study was to determine student perceptions of interest in reading using Ebooks in Semester 4 and 2 of the English study program at the University Prof. Dr. Hazairin S.H. Bengkulu. Researchers used a questionnaire to collect data on student perceptions and used descriptive qualitative in analyzing the data. The results of the data from the questionnaire were processed using the Microsoft Excel so that the data results were valid. The sample of this research is the students of second semester and fourth semester of the Department of English at the University Prof. Dr. Hazairin S.H., Bengkulu totaling 11 students. Samples taken amounted to 10 people. Based on the results of the study it was found that students had a total score of 61 students' perceptions. A score of 61 on the use of E-books in learning English which the results show students have a neutral perception (Best,w, John in Fitriani 2010), a neutral perception comes from their experience in the reading process, especially when they read independently. They feel they are still less interested in using E-books in reading because they feel E-books cannot improve their reading skills. The results showed that based on the analysis of the Likers score, the total score of students was 61, when viewed in the perception table, the classification of these values ​​was in neutral perception. The e-book is categorized as applicable to students in the second and fourth semesters of the English study program at Prof. University. Dr. Hazairin S.H. Bengkulu. So the conclusion of this research is that the students of the English Study Program at the University of Prof. Dr. Hazairin S.H. Bengkulu, some are interested and some are not interested in using E-books to improve their English reading skills. This is due to the lack of students' motivation to use e-books in learning and some students feel that their reading ability results increase when they read using e-books.